STATE OF STOCKS AND MODERN FISHERY OF ATKA MACKEREL PLEUROGRAMMUS MONOPTERYGIUS (PALLAS, 1810) IN THE OLYUTORSKY-NAVARINSKY AREA OF THE BERING SEA - A. O. Zolotov; O. G. Zolotov; Yu. K. Kurbanov (Известия ТИНРО, 2020)
Atka mackerel Pleurogrammus monopterygius is one of the mass species of fam. Hexagrammidae that inhabits the boreal and subarctic waters of the North Pacific and forms two large populations in its western and eastern parts. Reproductive range of the eastern, Aleutian population extends from the Gulf of Alaska, along Aleutian Islands to Commander Islands, with the main spawning grounds at the Aleutians and in the southeastern Bering Sea. From these areas, the fish at early stages of ontogenesis spread widely in system of the Bering Sea currents to the western-southwestern Bering Sea, where the atka mackerel aggregations are formed on the external shelf at prominent capes, as Cape Olyutorsky. Dynamics of the atka mackerel stock in the Olyutorsky-Navarinsky area in 1994–2019 is presented on the base of bottom trawl surveys, fishery statistics, and open NOAA data. After the period of low stock in the middle 1990s, the atka mackerel abundance increased sharply to the maximum in 2006–2008, when the spawning stock in this area was about 9.5 . 103 t and the commercial stock about 14.0 . 103 t. Since that time, trend to decreasing is observed, with the spawning stock 3.6 . 103 t and the commercial stock 5.6 . 103 t in 2013, and recent stabilization at the low level with slight decline continuing. A possible reason of the sharp increase in 2000s could be the intensive transport of the atka mackerel juveniles from the main spawning grounds at Aleutian Islands to the area at Cape Olyutorsky. The catches of atka mackerel in the Olyutorsky-Navarinsky area in 1994–2018 corresponded well with its stock dynamics.